The Fred factor - Aubrey Malden (Communicare)
So often we seem to speak in abstracts about marketing. We may all nod our heads when it comes to the importance of the basics of digging and delving into the marketplace and thoroughly researching the competition and looking at trend analyses. When we moreover talk about the importance of positioning our brand and differentiating it by means of both an impactful name and packaging that really do express the brand’s character, its DNA, we may all nod our heads again.